Medici del corpo contro terapeuti della parola: una riflessione su medicina e sofistica - Ioli, Roberta (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2013)
The aim of the present paper is to investigate the connection between ancient medicine and sophistry at the end of 5th century B.C. Beginning with analyses of some passages from the De vetere medicina (VM), De natura hominis (NH) and De arte, the article identifies many similarities between these treatises, on the one hand, and the sophistic doctrines, on the other: these concern primarily perceptual/intellectual knowledge and the interaction between reality, knowledge and language. Among the Sophists, Gorgias was particularly followed and imitated, as he was admired not only for his tremendous rhetorical skills, but also for his philosophically significant work On not being, which probably influenced various discussions in the Hippocratic treatises. However, if Gorgias argues in favor of language as dynastēs megas, the authors of VM, NH and De arte consider knowledge to be far more relevant and reliable than logos. These Hippocratic treatises criticize the philosophical thesis and the resulting kind of reductionism. Above all they defend the supremacy of medicine over any other art. By using the same argumentative and rhetorical strategies that were employed by Gorgias, these treatises reverse the thought of those Sophists who exalted only the technē tōn logōn.
Keywords: Sophistry; ancient medicine